PROFESSIONAL ACCOUNTING EDUCATION. - Moyer, C. A. (The Accounting Review, 1945)
Abstract Colleges and universities are attempting to serve the public by providing the type of education necessary to supply well-trained citizens who will fill a proper place in the society. In their accounting work, it is their desire to carry on a program, which will serve the profession. The author is surprised and perplexed at the antagonistic tone of occasional articles by both practitioners and educators. Mutual understanding is desirable. The profession looks to the educational institutions for the stock from which most of the future professional accountants will come. The educational institutions are training people for accounting careers and look to the public accountants for employment for many of their graduates. Thus the practitioner and the educator have mutual interests. Close cooperation should be beneficial to both. In the postwar period no one should lose sight of the fact that educational institutions want to serve the profession in providing adequate preparation for an accounting career; teachers are anxious to work with men in the profession in solving mutual problems which will arise; and men of experience.